Insights on the structure-performance relationship of polyphthalamide (PPA) composites reinforced with high-temperature produced biocarbon. Issue 45 (21st July 2020) - Gonzalez de Gortari, Mateo; Rodriguez-Uribe, Arturo; Misra, Manjusri; Mohanty, Amar K.
Abstract : Biocarbon-filled polyphthalamide composites were made, achieving comparable mechanical and thermal characteristics to talc-filled ones, at a lower density. Abstract : Reducing greenhouse gas emissions (GHG) in vehicles requires the use of lighter-weight materials. One possible strategy is using biomass-derived carbons (biocarbon), which have a lower density compared to traditional mineral based fillers. In this study, novel composites reinforced with 20 and 30 wt% of a biocarbon produced at high temperature (950 °C) were melt compounded with polyphthalamide (PPA), followed by injection molding, and compared to talc-filled composites. Mechanical tests were performed with ASTM standard samples for tensile, flexural and impact properties, alongside thermal, spectroscopic and morphological characterizations. Surface area and elemental composition of the biocarbon and talc particles were also determined. The biocarbon and talc composites had matching mechanical properties in most of the tests (3.7 GPa for the Young's modulus of the 20 wt% talc-filled composite versus 3.7 GPa for both 20 wt% biocarbon-filled composites), with all the properties surpassing those of the unfilled, neat PPA (Young's modulus of 2.4 GPa), and the biocarbon-filled composites have a lower density than the talc-filled ones (1.277 g cm −3 for the 20 wt% talc-filled composite versus 1.176 g cm −3 for both 20 wt% biocarbon-filled composites). The main influencing factors for the better performance of the biocarbon-PPA composites were found to be the similarity of particle size between the talc and the biocarbon.